Gram-scale photosynthesis of polyfunctionalized dihydro-2-oxypyrroles using 3DPAFIPN as a halogenated dicyanobenzene-based photosensitizer via a consecutive visible-light-induced electron transfer process - Mohamadpour, Farzaneh; Amani, Ali Mohammad (Frontiers in Chemistry, 2024)
Background Typically, organic dyes show lower excited state lifetimes, a key hindrance in the development of efficient photoredox processes. Due to their distinctive qualities and efficiency, a particular class of organic chromophores has drawn considerable interest from the scientific community. Thermally activated delayed fluorescence (TADF), is only seen in molecules with a minimal energy gap (usually less than 0.2 eV) between their lowest two excited states, i.e., singlet excited state (S1) and triplet excited state (T1), is a distinctive property of the molecules under study. Isophthalonitriles are a promising family of chromophores for use as organic photocatalysts because of the ease with which their redox potentials may be adjusted and the prolonged singlet excited states resulting from TADF. Methods A sustainable process for the photosynthesis of polyfunctionalized dihydro-2-oxypyrroles has been developed using the Michael-Mannich cyclocondensation of amines, dialkyl acetylenedicarboxylates, and formaldehyde. The development of a green radical synthesis strategy for this family of chemicals is discussed in detail in the current work. This work used a novel halogenated dicyanobenzene-based photosensitizer was used as a photocatalyst. It was dissolved in ethanol, exposed to air at ambient temperature, and triggered by a blue light-emitting diode as a renewable energy source. This project’s main goal is to use a novel conveniently accessible, reasonably priced donor-acceptor (D-A) based on halogenated cyanoarene. Findings When exposed to visible light, the 3DPAFIPN [2,4,6-tris(diphenylamino)-5-fluoroisophthalonitrile] photocatalyst, which is a thermally activated delayed fluorescence (TADF), can induce single-electron transfer (SET), providing a simple and green method that is highly effective, energy-efficient, and environmentally friendly. Also, we calculated the turnover number (TON) and turnover frequency (TOF) for polyfunctionalized dihydro-2-oxypyrroles. Gram-scale cyclization has also been shown to be a practical technique for use in industrial applications.